Magneto-Strain Effect in Double-Layer Film Systems - Z.M. Makukha; S.I. Protsenko; L.V. Odnodvorets; I.Yu. Protsenko (Журнал нано- та електронної фізики)
For the first time a theoretical study of magnetodeformation effect (MSE) in double-layer film materials is presented, taking into account the previous results obtained for single-layer films. When creating the elementary theory one derives the well-known coefficient for longitudinal strain coefficient (SC, ) for a double-layer film system of the type, “biplate”, without taking into account the possible processes of mutual diffusion of atoms. The MSE is quantified by the magnetic coefficient of the SC B  (1/)(/B), which describes the change of the film’s electrical resistance under its deformation in the external magnetic field. In the finite ratio for MSE, considered by the appropriate index for three possible orientations of the magnetic field relative to the direction of the flow of electric current (which coincides with direction of the longitudinal SC) the right-hand-side consists of the following values: R,  (resistivity), B (magnetic coefficient of resistivity) and second-order partial derivative  with respect to strain and magnetic field. The latter is not calculated from the first principles but is measured experimentally. Analyzing the ratio for the limiting cases for B, when d1 >> d2 and d1 << d2, leads to predicting as to how the SC depends on the size of the magnetic field.